METODE BIMBINGAN AGAMA ISLAM DALAM PENANAMAN AKHLAK TERHADAP ANAK JALANAN DI SEKOLAH ISLAM IMPIAN KOTA MAKASSAR - St Rahmatiah; Rahmaniar, A. Astiyani (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2023)
This journal aims to describe how the method of Islamic religious guidance in fostering street children’s morals at the Islamic dream school in Makassar City. This study uses a guidance approach. Primary Data Sources Data sources are informants who are considered competent in providing information about this research. In this study, the primary data source (key informant) was Febriansyah as the founder of the Islamic Dream School in Makassar City. The additional informants are Indriani school coaches, Zulfikar, Sahrani, and street children, namely Tasya, Saiful, Fadillah, Rendi, Karmila. Secondary data sources are data obtained to support primary data. Secondary data used includes literature studies by collecting data and studying by citing theories and concepts from a number of literary books, journals, magazines, newspapers or other written works. And utilize written documents, pictures, photographs, or other objects related to the aspects studied. The results of this study indicate that the coach’s efforts in cultivating morals towards street children are Murojaah, Dhuha prayer in congregation, Tahfidzul Qur’an, Memorizing daily prayers. Inhibiting factors The coach’s efforts in fostering morals towards street children are factor Environment, and Student presence in learning.